A Study Effect of Specific Absorption Rate in Human Head Model due to Electromagnetic Exposure - Mutalik, S.R.A.; Mat, M.H.; Zakaria, M.R.; Yusoff, M.I. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This study presents a numerical analysis of the specific absorption rate in the human head model due to electromagnetic exposure. A set of dipole antennas operating at 1800MHz and 2600MHz were located at the ear of human head model to investigate the effect of frequency on human head model. The maximum average of 1gram and 10gram of tissue have been presented to show the effect of the electromagnetic field in the human head model. A comparison of the mass averaged SAR in the head shows the 1g of SAR is quintuple at both 1800MHz and 2600MHz respectively.